Geotechnical investigations of the Sawatari Landslide in Shikoku, Japan - Bhandary, Netra Prakash; Yatabe, Ryuichi; Yagi, Norio; Yokota, Kinutada (Journal of Nepal Geological Society, 2000)
Many large landslides are found in various parts of Japan. Among them, the Sawatari Landslide in the Shikoku Region is quite different from others, as it contains expansive clays. This study focuses on the mineralogy, strength parameters, and index properties of the slip layer clay of the Sawatari Landslide. The study of clay mineralogy revealed significant chlorite and expansive chlorite content. The angle of residual shearing resistance of the slip layer soil containing expansive clay minerals is much smaller than that of the soil containing non-expansive minerals.